Kinetics and mechanism of free radical grafting of acrylamide onto tapioca starch. - Tung, Nguyen Thanh; Huy, Nguyen Quang; Khoi, Nguyen Van; Thang, Tran Vu (Vietnam Journal of Chemistry, 2012)
Graft polymerization of acrylamide (AM) onto tapioca starch has been carried out in aqueous solution using potassium persulfate as initiator. Dependence of graft yield upon monomer, starch and initiator concentration as well as reaction temperature is investigated by using gravimetry method. Rate equation obtained are: Rg = k[AM]1.045 [KPS]0.589 [Starch]0.533. The kinetics of grafting process has been evaluated and the activation energy within temperature 60-700C for starch-g-PAM synthesis is found to be 52.53kJ/mol. A suitable mechanism was also proposed to justify the results.